Globalization and its Implications for Education in Nigeria - O, David; O, Grace; E, Etelbert (Richtmann Publishing, 2011)
Globalization as the rapid increase in cross-border economic, social and technological exchange is not limited to industry andbusiness. Education systems being part of the information business can be seen as the core of globalization. This paper provides ananalysis of the relevant literature on the implications of globalization for education in Nigeria. The nature and objectives of globaleducation and the move towards standardized curricula were highlighted. Perceived barriers to globalization of education and the Nigeriansituation were also analyzed. This paper finally provides information and recommendations to those responsible for the planning of theeducational curricula for all levels of education in Nigeria